2011
DOI: 10.1111/j.1525-1594.2011.01206.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oxygenator Selection on Hemodynamic Energy Indicators Under Pulsatile and Nonpulsatile Flow in a Neonatal Extracorporeal Life Support Model

Abstract: This study compared the quality of perfusion delivered by two oxygenators--the hollow-fiber membrane Capiox Baby RX05 and silicone membrane Medtronic 0800--using hemodynamic energy indicators. The oxygenators were tested across varying flow rates and perfusion modes in a neonatal extracorporeal life support (ECLS) model. The experimental ECLS circuit included a Jostra HL-20 heart/lung machine with Jostra Roller pump, oxygenators with associated tubing and components, and a neonatal pseudo-patient. We used a 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…In our experiment, even at relatively higher flow rates, the pressure drop across the iLA membrane ventilator was low compared with traditional sililcone membrane and hollow fiber oxygenators (16). No difference was noted in terms of pressure drops at various rhythm disturbances and different assist ratios.…”
Section: Discussionmentioning
confidence: 46%
“…In our experiment, even at relatively higher flow rates, the pressure drop across the iLA membrane ventilator was low compared with traditional sililcone membrane and hollow fiber oxygenators (16). No difference was noted in terms of pressure drops at various rhythm disturbances and different assist ratios.…”
Section: Discussionmentioning
confidence: 46%
“…The pressure drop across the ECLS circuit is important to evaluate because an increased pressure drop correlates with a greater loss of hemodynamic energy and blood damage . Our results demonstrated that the total circuit pressure drops were similar in the ECLS circuit with the centrifugal pump , regardless of CRRT position.…”
Section: Discussionmentioning
confidence: 60%
“…The potential reduction in mechanical complications is one of the major reasons for making improvements in component materials and designs. Evaluation of the hollow‐fiber oxygenator in the lab demonstrated improved hemodynamics with decreased pressure drop across the hollow‐fiber oxygenator membrane indicating lower resistance to flow (8–11). This reduction in pressure should result in lower hemolysis and less inflammatory activation.…”
Section: Discussionmentioning
confidence: 98%